Beliefs about inevitable decline among home‐living older adults at risk of malnutrition: a qualitative study. Issue 6 (25th August 2020) - Payne, L.; Harris, P.; Ghio, D.; Slodkowska‐Barabasz, J.; Sutcliffe, M.; Kelly, J.; Stroud, M.; Little, P.; Yardley, L.; Morrison, L.
Abstract: Background: Approximately 14% of free‐living adults aged ≥65 years are at risk of malnutrition. Malnutrition screen and treat interventions in primary care are few, show mixed results, and the advice given is not always accepted and followed. We need to better understand the experiences and contexts of older adults when aiming to develop interventions that are engaging, optimally persuasive and relevant. Methods: Using the Person‐based Approach, we carried out 23 semi‐structured interviews with purposively selected adults ≥65 years with chronic health or social conditions associated with malnutrition risk. Thematic analysis informed the development of key principles to guide planned intervention development. Results: We found that individuals' beliefs about an inevitable decline in appetite and eating in older age compound the many and varied physical and physiological barriers that they experience. Also, we found that expectations of decline in appetite and physical ability may encourage resignation, reduce self‐efficacy to overcome barriers, and reduce motivation to address weight loss and/or recognise it as an issue that needs to be addressed. Fear of loss of independence may also reduce the likelihood of asking general practitioners for advice. Conclusions: The key findings identified include a sense of resignation, multiple different barriers to eating and a need for independence, each underpinned by the expectation of a decline in older adulthood. Interventions need to address misperceptions about the inevitability of decline, highlight how and why diet recommendations are somewhat different from recommendations for the general population, and suggest easy ways to increase food intake that address common barriers. Abstract : Using the Person‐based Approach, we interviewed adults aged ≥65 years with health or social conditions associated with malnutrition risk. Beliefs about inevitable decline in appetite and eating in older age can compound the diverse barriers to eating, and expectations of decline in appetite and physical ability may encourage resignation, reduce self‐efficacy to overcome barriers and reduce motivation to address weight loss. Interventions need to address misperceptions, highlight how and why diet recommendations are somewhat different from those for the general population, and suggest easy ways to increase food intake that address common barriers.